2017
DOI: 10.1177/1475921717707356
|View full text |Cite
|
Sign up to set email alerts
|

Toward identifying crack-length-related resonances in acoustic emission waveforms for structural health monitoring applications

Abstract: In this study, we focus on analyzing the acoustic emission waveforms of the fatigue crack growth despite the conventional statistics-based analysis of acoustic emission. The acoustic emission monitoring technique is a well-known approach in the non-destructive evaluation/structural health monitoring research field. The growth of the fatigue crack causes the acoustic emission in the material that propagates in the structure. The acoustic emission happens not only from the crack growth but also from the interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 34 publications
1
40
0
Order By: Relevance
“…Passive sensors detect signals generated by damage due to the evolution of the damage, which does not require an external excitation. Acoustic emission belongs to this category [11]. If damage is detected during flight, this can be a useful method.…”
Section: Literature Review On Structural Health Monitoring Technologiesmentioning
confidence: 99%
“…Passive sensors detect signals generated by damage due to the evolution of the damage, which does not require an external excitation. Acoustic emission belongs to this category [11]. If damage is detected during flight, this can be a useful method.…”
Section: Literature Review On Structural Health Monitoring Technologiesmentioning
confidence: 99%
“…These sensors were also used to detect the AE waveforms for simple pencil lead breaks AE in the past [8]. Efforts were made to retrieve the structural feature related information from the AE waveforms [9] Sagar et al [10] reported a relationship between AE and fracture parameters to estimate the crack geometry.…”
Section: State Of the Artmentioning
confidence: 99%
“…The detail of the dipole loading FEM parameters can be found in ref. [9]. We may hypothesize two physical phenomena to explain underlying physics behind the two types of AE waveforms.…”
Section: Two Types Of Simulated Ae Waveforms Corresponding To Two Ae mentioning
confidence: 99%
“…The phenomena related to crack resonance was identified through peak frequency based analysis. 9 Wavelet transform based frequency approach was efficiently utilized by Yang et al for the classification of different failure mechanisms of thermal barrier coatings. 10 Investigation on the damage behaviour of the thermal barrier coatings attacked by molten calcium-magnesium-alumino-silicate was executed using AE system by L.Yang, et al The discrimination of failure modes is obtained using wavelet packet transform technique.…”
Section: Introductionmentioning
confidence: 99%